KARAKTERISTIK PROTEIN DAN SENSORI DORAYAKI DARI EKSTRAK DAUN KELOR - Muhammad Faras M.L; Rostiati Dg. Rahmatu; Syahreni Kadir (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The objective of this research was to determine the optimal concentration of Moringa leaf extract to enhance the protein content and consumer preference of Moringa dorayaki cake. The study utilized five levels of treatments with varying concentrations of Moringa leaf extract (0%, 5%, 10%, 15%, and 20%) for protein analysis. The data analysis employed a Completely Randomized design with the Tukey’s HSD test for protein analysis, and a Randomized Block design (RBD) with 15 panellists for sensory tests. The results showed a significant effect of the Moringa leaf extract concentration on protein content, with concentrations of 0%, 5%, 10%, 15%, and 20% yielding protein contents of 6.81%, 8.71%, 9.16%, 10.28%, and 11.23%, respectively. The sensory test results indicated no significant effect, and the panellists enjoyed the Moringa dorayaki cake at all concentrations. Therefore, the optimal concentration for protein content was found to be 20%, while all concentrations were equally preferred by the panellists.